Self-healing polymers : from principles to applications - Binder, Wolfgang (Wolfgang H.) (Weinheim, Germany : Wiley-VCH, 2013)
This self-contained reference, written by a team of renowned international authors adopt a didactical approach to systematically cover all important aspects of designing self-healing polymers from concepts to applications - transferring lessons learnt from nature to materials science. It is the first to discuss the chemical and physical concepts for self-healing polymers, including aspects of biomimetic processes of healing in nature and tissue regeneration. Chapters will cover the design of self-healing polymers and explain the dynamics in these systems.
9.4 Concluding Remarks and Future Outlook10: Preparation of Nanocapsules and Core-Shell Nanofibers for Extrinsic Self-Healing Materials; 10.1 Selected Preparation Methods for the Encapsulation of Self-Healing Agents; 10.2 Mechanically Induced Self-Healing; 10.3 Stimuli-Responsive Self-Healing Materials; 10.4 Novel Approaches and Perspectives; Part Three: Supramolecular Systems; 11: Self-Healing Polymers via Supramolecular, Hydrogen-Bonded Networks; 11.1 Introduction; 11.2 Dynamics of Hydrogen Bonds in Solution; 11.3 Supramolecular Gels; 11.4 Self-Healing Bulk Materials; 11.5 Conclusions.
Includes bibliographical references and index.
Print version record.
Keywords: Polymerization; Polymers; Self-assembly (Chemistry); Self-Healing polymers; SCIENCE -- Chemistry -- Organic; Polymerization; Polymers; Self-assembly (Chemistry); Electronic books